(untitled) (Research, Society and Development, 2020)
Barriguda [Ceiba glaziovii (Kuntze) K.Schum.] is a tree species with high timber potential and widely used for recovery of degraded areas. The environmental characteristics directly influence the growth and development of this species, where the light availability is one of the most important. Thus, the objective of this work was to evaluate morphophysiological aspects of C. glaziovii plants under different shading levels. In a completely randomized design, we used five treatments and eight replications at 0% (under full sun), 30%, 50%, 70% and 90% levels of shading. Evaluations were performed 60 days after aerial part emergence. Data were subject to analysis of variance (ANOVA) by the F test, and in cases of significance, the polynomial regression analysis was performed. The shading conditions influenced the morphophysiological characteristics of C. glaziovii young plants. Shading above 70% provided favorable conditions for the production of C. glaziovii seedlings.